Companion Diagnostics for Targeted Cancer Drugs – Clinical and Regulatory Aspects - Olsen, Dana; Jørgensen, Jan Trøst (Frontiers in Oncology, 2014)
Companion diagnostics (CDx) holds the promise of improving the predictability of the oncology drug development process and become an important tool for the oncologist in relation to the choice of treatment for the individual patient. A number of drug-diagnostic co-development programs have already been completed successfully, and in the clinic, the use of several targeted cancer drugs is now guided by a CDx. This central role of the CDx assays has attracted the attention of the regulators, and especially the US FDA has been at the forefront in relation to developing regulatory strategies for CDx and the drug-diagnostic co-development project. For an increasing number of cancer patients the treatment selection will depend on the result generated by a CDx assay, and consequently this type of assay has become critical for the care and safety of the patients. In order to secure that the CDx assays have a high degree of analytical and clinical validity they must undergo an extensive non-clinical and clinical testing before release for routine patient management. This review will give a brief introduction to some of the scientific and medical challenges related to the CDx development with specific emphasis on the regulatory requirements in different regions of the world.